Lack of resistance in cotton against cotton leaf curl begomovirus disease complex and occurrence of natural virus sequence variants - S.M. PAUL KHURANA and KAJAL KUMAR BISWAS*, SHRUTI GODARA, N. SAINI (Indian Phytopathology, 2015)
A survey was made to study incidence of cotton leaf curl disease (CLCuD) in cotton fields at Indian Agricultural Research Institute (IARI), New Delhi for the last six years from 2009 to 2014. It was observed that CLCuD has increased from initial year to current year of study. The average disease incidence was found to be as high as 15.92% in 2013 and moderate of 8.4-9.2% in 2012 and 2014, and 2.1-6.4% in the years of 2009 to 2011. Out of 55 cotton varieties screened against CLCuD in field condition in 2013 and 2014, none was found to be resistant. The per cent plant infection varied with the cultivars and ranged from 0 to 46.4% in 2013 and 0 to 26.4% in 2014. However, based on the field study for both the years, seven varieties, P21-51, P-31, P1752, P5616, P5618, 12 P 4 and P 5628 were identified as tolerant varieties. In greenhouse condition, one hundred thirty three cotton cultivars including 73 varieties, 48 germplasm and 12 Bt cotton hybrids were screened through whitefly inoculation. None of the cultivars were found to be resistant to this disease. All the Bt hybrids tested were found to be highly susceptible. Of the 15 desi cotton (G. arboretum) varieties tested, none was infected by CLCuD. Whitefly transmission and nucleotide sequence analysis of coat protein (CP) and C2 gene determined that the causal agents of CLCuD were whitefly transmitted CLCuD-begomoviruses. Real time-PCR analysis and the analysis of CP and C2 gene indicated appearance of virus variants at IARI cotton field. Present study concluded increasing trend of CLCuD in cotton over the years is due to lack of resistance in cotton cultivars and occurrence of possible virus variants.